Poverty Alleviation Through The Role Of Women’s Social Capital - Putri Suci Asriani; Yessilia Osira (Journal of Agri Socio Economics and Business, 2019)
Position and role between men and women according to cultural context is the caused unbalance gender role of husband and wife function. Many cases of female subordinate are being caused women to between and trapped in family discomfort, because women personally need of psychosocial and physical are not fulfilled. Some intellectual potential women will have been able to optimize the potential quality of their human resources for a career and occupation an important position as a public leader. However, because of the dominance of her husband or the system in this situational society does not permit or allow women to work or to improve the quality of their education, the chance that maybe only once in her lifetime will be lost. The women never get a chance to work or to be a public leader. In order to answer the problem, it is necessary to have a model of women, consequently. The contribution of women in various poverty alleviation efforts can be seen and measured. The study done in Bengkulu Province. It is known that women in the research area always try to help men in overcoming economic difficulties. Economic activity in the research area that can be  done by women is relatively limited. Women make effort to overcome economic difficulties in their household, among others by diversifying their businesses (agriculture, trade, services, tourism), exerting the power to increase household income or income by mobilizing all household members to work, owe to meet the necessities of life, and saving expenditure. Those saving is beneficial in order to save money, to reduce the quota, to reduce the quality of food consumption, to migrate and get a job, and to ask for help from the family. Adaptive women empowerment model that can be applied as one of pverty eradication efforts through the effective implementation of strategic Gender Responsive Development (GRD).